2021
DOI: 10.1128/aem.01714-20
|View full text |Cite
|
Sign up to set email alerts
|

Multimodularity of a GH10 Xylanase Found in the Termite Gut Metagenome

Abstract: The functional screening of a Pseudacanthotermes militaris termite gut metagenomic library revealed an array of xylan degrading enzymes including Pm25, a multi-modular Glycoside Hydrolase (GH) family 10. Sequence analysis showed details of the unusual domain organization of this enzyme. It consists of one catalytic domain, which is intercalated by two Carbohydrate Binding Modules (CBMs) from family 4. The genes upstream of pm25 are susC-susD-unk suggesting Pm25 is a Xyn10C-like enzyme belonging to a polysaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 72 publications
0
18
2
Order By: Relevance
“…This result is lower than a previous study which found K m of 0.248 mM for the novel xylanase from fungi 52 . The K cat and K cat /K m values of the PersiXyn8 were higher than the results reported for xylanase from gut metagenome using beechwood xylan as substrate 53 . The PersiXyn8 was also active in the presence of various metal ions and inhibitors increasing the number of applications for the enzyme 49 , 54 .…”
Section: Discussioncontrasting
confidence: 73%
“…This result is lower than a previous study which found K m of 0.248 mM for the novel xylanase from fungi 52 . The K cat and K cat /K m values of the PersiXyn8 were higher than the results reported for xylanase from gut metagenome using beechwood xylan as substrate 53 . The PersiXyn8 was also active in the presence of various metal ions and inhibitors increasing the number of applications for the enzyme 49 , 54 .…”
Section: Discussioncontrasting
confidence: 73%
“…One of its open reading frames encodes a multimodular GH10, designated P. militaris 25 ( Pm 25). This enzyme is characterized by a discontinuous organization that includes the insertion of two tandem CBM4 domains (CBM4-1 and CBM4-2) within the catalytic GH10 xylanase domain (Table 1 ) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…This technique allows the visualization of enzyme penetration and migration along a constructed cellulose composite, and impacts of non-catalytic proteins and protein modules on enzyme migration. Three lines of investigation were pursued for proof of concept of the PACER assay: (1) comparative analysis of three endo -1,4-β-xylanases to assess the impact of protein size and presence of a CBM on enzyme migration through a formulated cellulose/azo-xylan matrix; (2) evaluation of two loosenins for their potential to increase xylanase migration through the formulated matrix, and (3) characterization of Pm 25, an endo -1,4-β-xylanase recently discovered from termite gut metagenome [ 44 ]. By simultaneously measuring product release and migration of enzymes through defined cellulosic materials, the PACER assay can uncover determinants of enzyme accessibility not detected through measuring release of soluble products alone.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a in depth characterization of full length and truncated variants of Pm 25 gene (Xyn10C-like enzyme- part of xylan utilization locus) was performed in order to understand the CBM role with unusual multimodularity. Results indicate that the CBM would act synergistically to improve the enzyme activity and its is more specific towards the xylan hydrolysis [ 44 ]. In turn, the metagenomic of gut symbionts sever as a strategy in novel enzyme identification that are potential with high enzyme activities.…”
Section: Molecular Characterization Of Microbial Symbiontsmentioning
confidence: 99%